PREFERENSI KONSUMEN TERHADAP BUAH APEL IMPOR DI TOKO BUAH HOKKY DAN PASAR TRADISIONAL AMPEL SURABAYA - Rahayu, Jeani Noviana; Fauziyah, Elys; Ariyani, Aminah HM (Program Studi Agribisnis Fakultas Pertanian Universitas Trunojoyo Madura., 2012)
This study aims to describe the characteristics of consumers who buy imported apples and analyze the attributes of consumer preferences in buying imported apples. The study was conducted at the Hokky fruit shop and the Ampel traditional market in Surabaya. Data analysis was done with descriptive and conjoint methods. The analysis showed that the attributes that a consumer preference in buying apple imports in order are the price, color, texture, size and packaging.